Comprehensive Analysis and Experimental Validation of an Improved Mathematical Modeling of Photovoltaic Array. (13th January 2015) - Bal, Satarupa; Anurag, Anup; Nanda, Mrutyunjaya; Sourav, Suman
Abstract : This paper proposes a simple, accurate, and easy to model approach for the simulation of photovoltaic (PV) array and also provides a comparative analysis of the same with two other widely used models. It is highly imperative that the maximum power point (MPP) is achieved effectively and thus a simple and robust mathematical model is necessary that poses less mathematical complexity as well as low data storage requirement, in which the maximum power point tracking (MPPT) algorithm can be realized in an effective way. Further, the resemblance of the P-V and I-V curves as obtained on the basis of experimental data should also be taken into account for theoretical validation. In addition, the study incorporates the root mean square deviation (RMSD) from the experimental data, the fill factor (FF), the efficiency of the model, and the time required for simulation. Two models have been used to investigate the I-V and P-V characteristics. Perturb and Observe method has been adopted for MPPT. The MPP tracking is realized using field programmable gate array (FPGA) to prove the effectiveness of the proposed approach. All the systems are modeled and simulated in MATLAB/Simulink environment.